Altered Functional Connectivity and Cognition Persists 4 Years After a Transient Ischemic Attack or Minor Stroke - Nicolas, Korinne; Goodin, Peter; Visser, Milanka M.; Michie, Patricia T.; Bivard, Andrew; Levi, Christopher; Parsons, Mark W.; Karayanidis, Frini (Frontiers in Neurology, 2021)
Background and Purpose— Altered executive functions and resting-state functional connectivity (rsFC) are common following a minor stroke or transient ischemic attack (TIA). However, the long-term persistence of these abnormalities is not well studied. We investigated whether there were cognitive and rsFC differences between (a) controls and minor cerebrovascular event (CVE) patients and (b) between CVE patients with and without an imaging confirmed infarct (i.e., minor stroke and TIA, respectively) at an average of 3.8 years following their event. Methods—Structural and resting-state imaging and cognitive assessments including the Montreal Cognitive Assessment, the Trail Making Task and the National Institute of Health (NIH) Cognition Toolbox were conducted on 42 patients (minor stroke= 17, TIA= 25) and 20 healthy controls (total N=62). Results—Controls performed better than patients on two measures of executive functioning (both p<.046) and had reduced rsFC between the frontoparietal and default mode networks (FPN and DMN, respectively; p=.035). No cognitive differences were found between minor stroke and TIA patients, however, rsFC differences were found within the FPN and the DMN (both p<.013). Specifically, increased connectivity within the FPN was associated with faster performance in the minor stroke group but not the TIA group (p=.047). Conclusions— These findings suggest that transient or relatively minor cerebrovascular events are associated with persistent disruption of functional connectivity of neural networks and cognitive performance. These findings suggest a need for novel interventions beyond secondary prevention to reduce the risk of persistent cognitive deficits.